2009
DOI: 10.1002/chem.200802052
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Cyclopropanation of Alkenyl Silanes by Diazoalkanes: Evidence for a Pd0 Mechanism

Abstract: Alkenyl silanes are efficiently converted to the corresponding silyl cyclopropanes in the presence of a slight excess of diazomethane (2-4 equiv) and a low loading of Pd(OAc)(2) (<0.5 mol %). Diazoethane and diazobutane can also be employed and yield silyl cyclopropanes with diastereoselectivities of up to 10:1 for the trans isomer. When conducted on a 4 g scale, the reaction only required a catalyst loading of 5x10(-3) mol %, which corresponds to a turnover frequency of 40,000 h(-1). Competition experiments r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 113 publications
0
15
0
Order By: Relevance
“…Experimental evidence suggesting that the olefin-complexed Pd 0 species is a highly active catalyst has been obtained, mostly likely to be involved in a resting state in the catalytic cycle (Scheme 3). [16] Scheme 3. Cyclopropanation catalyzed by a Pd 0 complex.…”
Section: Pd-catalyzed Cyclopropanationmentioning
confidence: 99%
“…Experimental evidence suggesting that the olefin-complexed Pd 0 species is a highly active catalyst has been obtained, mostly likely to be involved in a resting state in the catalytic cycle (Scheme 3). [16] Scheme 3. Cyclopropanation catalyzed by a Pd 0 complex.…”
Section: Pd-catalyzed Cyclopropanationmentioning
confidence: 99%
“…The already‐described Pd 0 ‐based catalysts for these transformations contain phosphanes or olefins as ancillary ligands 9d. 11c On the other hand, Pérez and co‐workers have reported that group 11 metal complexes containing N‐heterocyclic carbene (NHC) ligands are active catalysts towards carbene transfer from ethyl diazoacetate (N 2 CHCO 2 Et; EDA) to several saturated or unsaturated substrates 4q.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Cyclopropanation of unsaturated moieties by generating carbenoids using diazo compounds in the presence of transition metal-catalysts is a particularly versatile method reported in the literature, even if usually applied only for low molecular weight olefins. [10] Frequently used metal-catalysts based on palladium and rhodium, [11][12][13][14] but also Cu(I/II)-based catalysts were considered for such cyclopropanations. [15][16][17][18] Cyclopropanation of poly(diene)s, like poly(isoprene) (PI) or poly(butandiene), are only rarely known examples in the literature.…”
Section: Introductionmentioning
confidence: 99%